ANALYSIS OF THE PERCEPTION OF EMPLOYEES ABOUT THE IMPLEMENTATION OF THE 5S METHOD IN A METALLURGICAL COMPANY - Marcheti, Lucas Endrigo; Magrini, Rosemary Chiuchi; Pandolfi, Marcos Alberto Claudio (Revista Interface Tecnológica, 2022)
The objective of this paper was to seek understanding of the 5S applied in the settings on the optics of employees. To this end, it was based on theoretical surveys based on the publication of books, monograph and articles on the 5S method. Following presents a case study in a metallurgical company located in the city of Matão, state of São Paulo, a survey was conducted with 50 employees with questionnaire application. To compare the results, a descriptive statistics analysis was performed using data tabulation, considering the discrete variables and the average frequency analysis. The questionnaire was direct and objective to see which sensor sent improvements with the implementation of the 5S Program for a company. For the 5S analysis, the factors (Great, Good and Regular) were used, these were tabulated in spreadsheets using the Microsoft Excel application, and a questionnaire was used as a note, which were used for 5S analysis. It will be concluded that this study was successful, because it achieved the proposed objectives, it also provided a useful information center, with fundamental concepts in the implementation of the 5S method.  Being that, the 5S of the parameters for improvement in all sectors of an organization.  It should be noted that for the application of the 5S method in companies, to be successful it is necessary to accept employees.
Keywords: Method 5S; Application; Case study